Interactive Learning Multimedia Articulate Storyline as an Alternative Media to Improve Elementary Students’ Critical Thinking Skills - Alanise Moriska; Muhammad Hanif (Universitas Pendidikan Ganesha, 2024)
Due to the lack of use of learning media in the mathematics learning process, students become passive and uninterested in participating in the learning process. The monotonous learning process causes students' critical thinking abilities to be weak and underdeveloped. Therefore this research aims to analyze the influence of learning activities using Articulate Storyline interactive learning multimedia on analytical and critical thinking skills in sixth-grade elementary school students. This research employed a quantitative approach with experimental research methods (Quasi-Experimental). The type of sampling used was the purposive sampling technique. The research instrument utilized nine HOTS-type description test questions. Data were analyzed through several tests, including normality, homogeneity, and hypothesis tests. In hypothesis testing, the Independent Sample T-Test was used, and a Sig (2-tailed) value of (0.033 < 0.05) was attained, so it was inferred that there was a difference between students who were taught using Articulate Storyline interactive learning multimedia and students who were taught using conventional learning media. The Paired Sample T-test in the experimental class also obtained a significance value of 0.000 < 0.05, suggesting a significant difference in the average test scores before and after treatment. It could be concluded that using Articulate Storyline interactive learning multimedia influenced sixth-grade elementary school students' analytical and critical thinking skills. This research implies that teachers can use Articulate Storyline interactive learning multimedia to improve students' critical thinking analysis and evaluation skills in mathematics learning.